A TSF Control Strategy With Zero Voltage Modulation in Interval Segmented for Permanent Magnet-Assisted Switched Reluctance Motor - Chaozhi Huang; Renquan Xiao; Yong Xiao; Chengyi Gong (IEEE Access)
Aiming at the problems of large torque ripple in permanent magnet-assisted switched reluctance motor (PMa-SRM) under conventional voltage pulse width modulation (PWM) method. A torque sharing function (TSF) control strategy with interval segmented zero-voltage modulation is proposed in this paper. Firstly, the zero voltage is decentralized by optimizing the PWM modulation method. Secondly, the control interval is divided and a segmented TSF based on hyperbolic tangent function transformation is proposed tailored to the torque characteristics. Then, the PWM variable duty cycle control is carried out according to the inductance characteristics. In the single-phase conduction region (SpC), the optimal duty cycle is predicted by using the deadbeat predictive control (DPC); in the two-phase exchange region (TpE), the duty cycle function is designed for each interval, and the duty cycles of the incoming and outgoing phases are obtained online through the torque error. Finally, simulations and experimental verification of the 6/20 PMa-SRM prototype confirm that the proposed control strategy to have good performance in torque ripple suppression.